Screening Effectiveness of The Leaf Extract of Psidium guajava, Euphorbia hirta, and Piper betle L. as Antidengue - AGYA GHILMAN FAZA; Hudiyono .; Ratih Puspita Febrinasari (Nexus Biomedika, 2016)
Introduction: Dengue Hemorrhagic Fever (DHF) is an infectious disease caused by dengue virus which commonly found in the tropic and sub-tropic region. Nowadays, the main treatment of DHF is supporting therapy by giving a replacement fluid. However, the number of cases and deaths due to dengue infection in Indonesia still high enough. Another solution to fix this problem is using Indonesians native plants which potentially has antiviral effect for dengue virus, such as guava leaf (Psidium guajava), patikan kerbau leaf (Euphorbia hirta), and betel leaf (Piper betle L.). The aim of this study is to determine the effectiveness of the leaf extract of guava (Psidium guajava), patikan kerbau (Euphorbia hirta), and betel (Piper betle L.) as antidengue in vitro. Methods: This study was laboratory experimental research. The subject of this research was dengue virus serotype 2 strain New Guinea C (DENV2 NGC) which was infected into Huh-7 cell line. The study was held in two places, they were Virology and Biology Molecular Laboratory, Department of Microbiology, Faculty of Medicine, University of Indonesia and Pharmaceutical Laboratory, Faculty of Mathematic and Science, Sebelas Maret University. The study was conducted in 2 parts. First, dengue virus solution was mixed with herbal extract in well which its bottom contained Huh-7 cell monolayer to obtain percent infectivity by FFU assay. Second, Huh-7 cell monolayer was exposed to the herbal extract solution to obtain percent viability by MTT assay. The effectiveness of herbal extract was based on two criterias, there were average percent infectivity 20% and average percent viability > 50%. Results: The leaf extract of Psidium guajava, Euphorbia hirta, and Piper betle L. have average percent infectivity respectively: 7.4%, 65.3%, and 68.4%. While the average percent viability of them were: 88.7%, 95.3%, 96.2%. Conclusion: The leaf extract of Psidium guajava is effective as antidengue in vitro. Keywords: Psidium guajava, Euphorbia hirta, Piper betle L., dengue virus serotype 2 strain New guinea C (DENV2 NGC), Huh-7 cell